Influence of heart rate increase on uncorrected pre-ejection period/left ventricular ejection time (PEP/LVET) ratio in normal individuals. - Cokkinos, D V (1976)
In 26 normal volunteers, increase in heart rate from mean 73-94 +/- 1-97 to 103-61 +/- 2-72/min, by either intravenous atropine administration or rapid right atrial pacing, produced definite changes in the uncorrected systolic time intervals. As expected, total electromechanical systole (QS2) and left ventricular ejection time (LVET) were shortened, while the pre-ejection period (PEP) was unaffected. There was a consistent and significant increase of the PEP/LVET ratio (P less than 0-001). It is postulated that when this ratio is taken to express left ventricular contractility, it should probably be corrected for heart rate. Appropriate regression equations for such a correction were calculated (PEP/LVET=0-249 + 0-0168 HR).